Accidental hypothermia and impaired temperature homoeostasis in the elderly. Issue 6057 (5th February 1977) - Collins, K J; Dore, C; Exton-Smith, A N; Fox, R H; MacDonald, I C; Woodward, P M
Abstract : A longitudinal study of the age-related decline in thermoregulatory capacity was made in 47 elderly people to try to identify those at risk from spontaneous hypothermia. During the winters of 1971-2 and 1975-6 environmental and body temperature profiles were obtained in the home, and thermoregulatory function was investigated by cooling and warming tests. Environmental temperature and socioeconomic conditions had not changed but the body core-shell temperature gradients were smaller in 1976, indicating progressive thermoregulatory impairment. People at risk of developing hypothermia also seem to have low resting peripheral blood flows, a nonconstrictor pattern of vasomotor response to cold, and a higher incidence of orthostatic hypotension.